SISTEM PENERIMAAN MURID BARU (SPMB) ONLINE BERBASIS WEB PADA SMKS MAESTRO SEPATAN - Agung Adriansyah; Norita Sinaga; Ahmad Yayan Sopian; Arian Aldi Putra; Akuila Yoel At; Ahmad Imron Rossdi; M.Nasrulloh; Jati Alfatih; Najib Fadhilah; Ridwan Nur Janni; Khafiansach; Sulton Hasanudin (Abdi Jurnal Publikasi, 2026)
This study aims to design and develop an Online New Student Admission System (SPMB) based on a web platform at SMKS Maestro Sepatan. The system is developed using native PHP and a MySQL database with a modern responsive interface. The main features of the system include an informative landing page, a multi-step registration form, online document upload, a student panel, and a complete admin panel for data management and website content administration. The system development method uses the waterfall model, which consists of requirements analysis, system design, implementation, testing, and maintenance. The results of the study indicate that the system is able to improve the efficiency of the new student admission process, simplify data management, and provide information transparency for prospective students and the school administration.